2020
DOI: 10.21203/rs.3.rs-43515/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CircPVT1 Promotes Bladder Cancer Progression by Acting as a ceRNA for miR-140-3p to Target TRPS1

Abstract: Background: Bladder cancer (BC) is one of the most malignancy tumor in the urinary system. Therefore, further studies are needed to revealed the molecular mechanism of BC progression and development. Previous study demonstrated that the deregulation of circRNAs can regulate cell biological functions in tumorigenesis and development. However, the roles of circPVT1 in BC have not yet been revealed. Materials and methods: The expression level of circPVT1, miR-140-3p, and TRPS1 were measured by RT-PCR in BC tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Some studies have shown that some circRNAs are dysregulated in bladder cancer and can promote the progression of bladder cancer, such as circRIP2, circACVR2A, hsa_circ_0001361, and circMETTL3, and could affect bladder cancer cells' proliferation and metastasis [ 9 12 ]. At present, noninvasive urine detection, methylation detection products, and new molecular biomarker (circRNA and lncRNA) maybe the new therapeutic targets and the future development trends in bladder cancer [ 13 ]. It is suggested that circRNA can be used as a good biomarker and therapeutic target for early diagnosis and prognosis of bladder tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that some circRNAs are dysregulated in bladder cancer and can promote the progression of bladder cancer, such as circRIP2, circACVR2A, hsa_circ_0001361, and circMETTL3, and could affect bladder cancer cells' proliferation and metastasis [ 9 12 ]. At present, noninvasive urine detection, methylation detection products, and new molecular biomarker (circRNA and lncRNA) maybe the new therapeutic targets and the future development trends in bladder cancer [ 13 ]. It is suggested that circRNA can be used as a good biomarker and therapeutic target for early diagnosis and prognosis of bladder tumors.…”
Section: Introductionmentioning
confidence: 99%